2017
DOI: 10.1111/pace.13166
|View full text |Cite
|
Sign up to set email alerts
|

Roles of impaired intracellular calcium cycling in arrhythmogenicity of diabetic mouse model

Abstract: The type 2 diabetic mouse hearts show impaired repolarization, Ca handling homeostasis, and cardiac conduction reserve, leading to vulnerability of spatially discordant alternans development and induction of VA. Altered Ca -handling protein expressions probably underlie the molecular mechanisms of arrhythmogenicity in the type 2 diabetes animal model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Direct evidence that diabetes-related aberrant Ca 2+ homeostasis can contribute to reentrant mechanisms of arrhythmia was obtained by Chou et al (2017) who showed that optically mapped hearts from obese db/db mice exhibit concordant Ca 2+ /Vm alternans at lower stimulation frequencies than controls. The authors attributed it to lower expression levels of RyR2 and enhanced activity of CaMKII.…”
Section: Mechanisms Of Ca 2+ Dependent Arrhythmia mentioning
confidence: 99%
“…Direct evidence that diabetes-related aberrant Ca 2+ homeostasis can contribute to reentrant mechanisms of arrhythmia was obtained by Chou et al (2017) who showed that optically mapped hearts from obese db/db mice exhibit concordant Ca 2+ /Vm alternans at lower stimulation frequencies than controls. The authors attributed it to lower expression levels of RyR2 and enhanced activity of CaMKII.…”
Section: Mechanisms Of Ca 2+ Dependent Arrhythmia mentioning
confidence: 99%
“…Action potential duration at 80% repolarization (APD 80 ) and Ca i transient duration at 80% decay (Ca i TD 80 ) were measured at two PCLs of 200 and 100 ms. [12] The differences between the longest and shortest APD 80 and Ca i TD 80 were used to represent APD 80 and Ca i TD 80 dispersion. To estimate conduction velocity (CV), we measured the distance and conduction time between the earliest activation point and two epicardial points: one was from the pacing site to the left ventricular apex (CV IR ), and the other was along an axis parallel to the atrioventricular ring (CV non−IR ).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo electrophysiological study was performed after reperfusion for 10 min. [12] Burst pacing (pacing cycle length (PCL) = 50 ms, 2 sec) and extrastimulus pacing (S 1 -S 4 ) were applied to test VT (≥ three consecutive premature ventricular beats) inducibility to all mice. The severity of inducible VT was classified as < 10 beats, between 10 to 30 sec, and > 30 beats.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ranolazine administration ameliorates conduction inhomogeneity in regional IR injury. Stud-ies have shown reduced cardiac conduction reserve in diabetic animal models[24][25][26] . Therefore, propagation of activity through the myocardium in diabetic hearts is more sensitive to conditions influencing cellular excitability or intercellular electrical coupling.…”
mentioning
confidence: 99%